Effect of incineration, co‐incineration and combustion on TSE hazards in category 1 animal by‐products - EFSA Panel on Biological Hazards (BIOHAZ); Ana Allende; Avelino Alvarez‐Ordóñez; Valeria Bortolaia; Sara Bover‐Cid; Alessandra De Cesare; Wietske Dohmen; Laurent Guillier; Lieve Maria Herman; Liesbeth Jacxsens; Lapo Mughini‐Gras; Maarten Nauta; et al. (EFSA Journal)
Abstract The European Commission requested EFSA to assess the effect of incineration, co‐incineration and combustion of Category 1 animal by‐products (ABP) on the BSE/TSE hazards in ash resulting from these treatments. The presence of residual TSE hazards is assessed by detection of prion infectivity or seeding activity. TSE agents or prions are challenging to inactivate completely using heat‐based methods. Different TSE strains exhibit varying degrees of thermoresistance. Based on available studies at temperatures 120–134°C, the C‐BSE strain is more thermoresistant than other evaluated strains. The vast majority of Category 1 ABP is rendered into ‘meat and bone meal’ prior to incineration/co‐incineration/combustion. Scenarios involving co‐incineration for cement production do not need to be considered because all ash is incorporated into the cement. It is not possible to generalise the time/temperature combinations to which Category 1 ABP are subjected across all processes. Due to the challenges in precisely measuring the temperature and residence time in industrial systems, and the wide range of system designs and operating conditions, it can only be assumed that Category 1 ABP are exposed to at least the legal requirements as determined by the conditions of the gas produced or injected into the process: 850°C for 2 s or 1100°C for 0.2 s. The limited sensitivity of the method used in a study involving C‐BSE at 1000°C for 20 min prevented a conclusive exclusion of residual C‐BSE prions.. Therefore, it is not possible to exclude – with high certainty (> 99%) – the presence of residual BSE/TSE hazards in ash produced from the incineration, co‐incineration or combustion of Category 1 ABP. It is recommended to generate data on the actual reduction of infectivity in ‘meat and bone meal’ spiked with thermoresistant TSE field strains after treatment with the time/temperature combinations required by the legislation or specific industry processes.